2014
DOI: 10.1111/anae.12730
|View full text |Cite
|
Sign up to set email alerts
|

A review of the scope and measurement of postoperative quality of recovery

Abstract: SummaryTo date, postoperative quality of recovery lacks a universally accepted definition and assessment technique. Current quality of recovery assessment tools vary in their development, breadth of assessment, validation, use of continuous vs dichotomous outcomes and focus on individual vs group recovery. They have progressed from identifying pure restitution of physiological parameters to multidimensional assessments of postoperative function and patient-focused outcomes. This review focuses on the progressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
118
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(124 citation statements)
references
References 84 publications
0
118
0
3
Order By: Relevance
“…In a recent narrative review of the measurement of the quality of recovery, Bowyer et al define early recovery as encompassing factors important for hospital discharge (physiologic stability, pain, nausea, gastrointestinal function), intermediate recovery as the first few weeks after surgery (nociceptive, emotional functional, and cognitive recovery), and late recovery as more than six weeks after surgery (focusing on poor functional recovery, persisting pain, nausea, and cognitive decline). 12 Qualitative work by our group and others support these suggestions. Urbach et al interviewed inpatients within two weeks of major abdominal surgery and identified the major themes: basic physical limitations (''transitioning from a lying position to sitting or standing''), basic activities of daily living (bathing, dressing, and grooming), and physical and psychological symptoms (pain, visceral function, sleep, and mood).…”
mentioning
confidence: 70%
See 1 more Smart Citation
“…In a recent narrative review of the measurement of the quality of recovery, Bowyer et al define early recovery as encompassing factors important for hospital discharge (physiologic stability, pain, nausea, gastrointestinal function), intermediate recovery as the first few weeks after surgery (nociceptive, emotional functional, and cognitive recovery), and late recovery as more than six weeks after surgery (focusing on poor functional recovery, persisting pain, nausea, and cognitive decline). 12 Qualitative work by our group and others support these suggestions. Urbach et al interviewed inpatients within two weeks of major abdominal surgery and identified the major themes: basic physical limitations (''transitioning from a lying position to sitting or standing''), basic activities of daily living (bathing, dressing, and grooming), and physical and psychological symptoms (pain, visceral function, sleep, and mood).…”
mentioning
confidence: 70%
“…At the present time, there is no perfect measure of postoperative recovery, but there have been many new instruments introduced since the systematic review by Kluivers et al, 14 and some measures missed from a subsequent review. 12 The psychometric properties of the newer instruments should be identified and evaluated. Ideally, validation studies should be performed for specific settings, patient populations, and time points.…”
Section: Future Directionsmentioning
confidence: 99%
“…As recovery is defined by the stakeholder, current clinical recovery assessment tools differ in their definition of recovery, their breadth and timing of assessment, and overall validation, all of which reflect the original focus for developing the tool. 34 Traditional recovery assessment tools were institutional and focused on the provider, limiting assessment to addressing restitution of physiological parameters in the immediate postoperative period. 35 Historically, factors with a direct impact on discharge readiness and institutional cost were assessednausea and vomiting, severe pain, 36-39 psychological distress, 37,38,[40][41][42] and basic physiological function.…”
Section: Measurement Of Recoverymentioning
confidence: 99%
“…Traditionally, QoR has focused on clinically physiological outcomes, but nowadays the focus has changed to multidimensional postoperative function and patient-focused outcomes (Bowyer et al 2014). A concept analysis suggests that postoperative recovery can be defined as an energy-requiring process until the preoperative level of normality and wholeness regarding physical, psychological, social and habitual functions has been restored (Allvin et al 2007).…”
Section: Quality Of Recoverymentioning
confidence: 99%